موقف حوزة النجف الاشرف من التطورات الداخلية في ايران أواخر العهد القاجاري - عجة حسنين عبد الكاظم; رديف زهراء عباس (Journal of College of Education, 2018)
The scientific estate in Najaf played an important role during the Qajari era. It is remarkable that the influence of the estate on the Iranian people increased in the late Qajari era in a manner that raised the fears of the Qajar Shahs. At that time, the scientific estate of Najaf adopted positions opposed to the Qajari authority, which concentrated on expelling Persia from Western influence. European countries, especially Britain, to gain economic and political privileges detrimental to the interest of Persia, and no doubt that the strength on the positions of the estate religious influence in Persia as the supreme religious reference to the Persians, and then it was able to force the Shahat in the late era I am going to make concessions to their people and the Najaf estate. The influence of the scientific estate of Najaf al-Ashraf in the abolition of NasirAl-ddin Shah Tobacco franchise, and after the revolution in 1905 supported the estate of Najaf Ashraf Persians against the government of Muzaffar Al-ddin Shah and was able to force him to adopt constitutional demands and grant many aspects of democracy to his people, and after the death and the arrival of his son Mohammed Ali Shah shaken things again because of the shah shunned the new concessions made by his father to his people, stood the references of the scientific estate in Najaf, a solid position forced him to retreat, and quickly was deposed and the installation of his son Ahmed Shah based on the desire of the estate, He said In spite of the success of the February 1921 coup, Reza Khan knew how to approach the scientific estate of the Najaf al-Ashraf and take advantage of its influence. To overthrow the Qajari rule, which has already been done.